THE USE OF INTERMEDIARIES IN THE PERFORMANCE OF SALES ACTIVITIES BY PHARMACEUTICAL ENTERPRISES (INNOVATIVE ECONOMY, 2023)
Penkova О.H. THE USE OF INTERMEDIARIES IN THE PERFORMANCE OF SALES ACTIVITIES BY PHARMACEUTICAL ENTERPRISESPurpose. The aim of the article is to analyse the expediency of using intermediaries in the implementation of sales activities by pharmaceutical enterprises, as well as to determine the algorithm for selecting an intermediary enterprise, taking into account the peculiarities of the sale of pharmaceutical products̈.Methods of research. General scientific and special methods were used in the research process, in particular: analysis – in the process of determining the goal and directions of the effective sales policy of the pharmaceutical enterprise; induction and deduction – at the stage of collecting, systematizing and processing the necessary information; abstract and logical – for the formation of theoretical conclusions regarding the significance of the use of intermediaries in the implementation of sales activities by pharmaceutical enterprises.Findings. It has been investigated that the integrated product sales system within the framework of the pharmaceutical activities of national enterprises is a set of specific methods of researching markets, finding potential consumers, analysing the existing needs of consumers of this product, forming and implementing innovative promotion channels using modern systems and digitalization, conducting advertising campaigns. The main sales channels and a set of procedures for promoting finished pharmaceutical products to the market with the help of intermediary enterprises are characterized.Originality. The substantiation of the expediency of using intermediaries in the implementation of sales activities by pharmaceutical enterprises has gained further development.Practical value. It was substantiated that any pharmaceutical enterprise needs to rationally form and organize the process of selling products to the final consumer in order to organize effective sales activities. This will have a positive effect on reducing costs and expanding the possibilities of offering additional services. Specialized intermediaries can help pharmaceutical enterprises in this.Key words: intermediaries, sales activity, pharmaceutical enterprises, pharmacy bases, pharmacies, internet sales, digitalization.
Keywords: intermediaries; sales activity; pharmaceutical enterprises; pharmacy bases; pharmacies; internet sales; digitalization